Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to understand Apery's 1978 proof that $\zeta(3) = \displaystyle \sum_{n=1}^\infty \frac{1}{n^3}$ is irrational. The idea behind the proof is to find an 'accelerated' series for $\zeta(3)$ which converges too fast to $\zeta(3)$, thus proving that $\zeta(3)$ cannot be rational. In particular, a particular quantity is defined:

$$e_{n,k} = \displaystyle \sum_{m=1}^k \frac{(-1)^{m-1} (m!)^2 (n-m)!}{2m^3 (n+m)!},\quad k \leq n.$$

The key is to show that $\displaystyle \lim_{n \rightarrow \infty} e_{n,k} = 0$ uniformly in $k$, and I have no idea why this sum converges to 0. Any ideas?

share|cite|improve this question
What source are you using as a reference? I do not recall actually having to examine the $e_{n,k}$ directly, but rather some related sums involving the individual terms in $e_{n,k}$. In any case, a good readable account is in "A PROOF THAT EULER MISSED. AP´ERY’S PROOF OF THE IRRATIONALITY OF $\zeta(3)$, AN INFORMAL REPORT", by van der Poorten, available at his website, – Andrés Caicedo Mar 6 '11 at 18:03
A link to the article by Alf van der Poorten is this . The quantity you mention appears in section 3. – Américo Tavares Mar 6 '11 at 18:20
@Americo: Not really, the sum itself is not needed. In section 3, the individual terms that make up $e_{n,k}$ are used in other sums. (Also, note that the version I linked to is slightly more updated that the printed article.) – Andrés Caicedo Mar 6 '11 at 18:45
@Andres: Concerning the sum that's right it is not needed for proving the irrationality of $\zeta (3)$. Anyhow the sum I referred to is $\sum_{k=1}^{N}\frac{(-1)^{k}}{2k^{3}\binom{N+k}{k}\binom{N}{k}}\rightarrow 0 $ as $N\rightarrow \infty $. According to my calculations $\left\vert \sum_{k=1}^{N}\frac{(-1)^{k}}{2k^{3}\binom{N+k}{k}\binom{N}{k}}% \right\vert <\frac{1}{2(N+1)}$. – Américo Tavares Mar 6 '11 at 19:37
@Americo: You are right (and your estimate is easier than what I was getting). – Andrés Caicedo Mar 6 '11 at 19:41
up vote 18 down vote accepted

By the triangular inequality, $|e_{n,k}|\leqslant\frac12 a_n$ with $$ a_n=\sum_{m=1}^nb_{n,m},\qquad b_{n,m}=\frac{(m!)^2(n-m)!}{m^3(n+m)!}, $$ hence the desired uniform convergence holds as soon as $a_n\to0$.

To prove that $a_n\to0$, note that $$ b_{n,m}=\frac{(m-1)!(m-1)!(n-m)!}{m(n+m)!}\leqslant\frac{(m-1)!(m-1)!(n-m)!}{(n+m)!}, $$ and use twice the fact that $i!j!\leqslant (i+j)!$ for every nonnegative integers $i$ and $j$. This yields $$ b_{n,m}\leqslant\frac{(n+m-2)!}{(n+m)!}=\frac1{(n+m-1)(n+m)}=\frac1{n+m-1}-\frac1{n+m}. $$ Thus $a_n$ is bounded by a telescoping sum, namely $$ a_n\leqslant\sum_{m=1}^n\left(\frac1{n+m-1}-\frac1{n+m}\right)=\frac1{n}-\frac1{2n}=\frac1{2n}, $$ This shows that $|e_{n,k}|\leqslant\frac1{4n}$ for every $n\geqslant1$ and uniformly over $k\leqslant n$, hence the proof is complete.

Edit One can refine the estimates above, taking into account the variations of the sequence $(b_{n,m})_{1\leqslant m\leqslant n}$ for some fixed $n$, which is nonincreasing on $1\leqslant m\leqslant m_n$ for some $m_n\approx n/\sqrt2$ and nondecreasing on $m_n\leqslant m\leqslant n$. Thus, $|e_{n,k}|\leqslant\frac12 b_{n,1}+\frac12 b_{n,n}$. Hence, $n^2e_{n,k}\to\frac12 $ uniformly over $k$.

share|cite|improve this answer
+1, Very nice solution! – Eric Naslund May 16 '11 at 17:01
+1, Very nice this general method. – Américo Tavares May 16 '11 at 17:16
@Didier: In the edit, which is the technique/argument one should use to find $m_{\text{min}}\approx n/\sqrt{2}$ ? – Américo Tavares May 17 '11 at 17:32
@Américo: One can estimate the ratio $b_{n,m}/b_{n,m+1}$ and compare it to $1$. – Did May 17 '11 at 17:33
@Didier: I verified that for $m\approx n/\sqrt{2}$ the sequence $b_{n,m}/b_{n,m+1}\rightarrow 1$ (as $n\rightarrow \infty $). – Américo Tavares May 17 '11 at 18:05

Update: edited text and formatting.

We can write the sum $e_{n,k}$ in the form (see section 4 of this article by Alf van der Poorten)

$$e_{n,k}=\sum_{m=1}^{k}\frac{(-1)^{m-1}}{2m^{3}\dbinom{n}{m}\dbinom{n+m}{m}}, \quad (1\leq k\leq n).$$

Let $u_{n,m}=m^{3}\binom{n}{m}\binom{n+m}{m}$. If $1=m\leq n$, then $u_{n,m}=n\left( n+1\right)$. To show that $u_{n,m}>n(n+1)$ for $1<m\leq n$ we consider the following two cases:

  • if $1<m=n$, then $u_{n,m}=n^{3}\binom{2n}{n}>n(n+1)$;

  • if $1<m\leq n-1$, then $m^{3}\binom{n}{m}\geq m^{3}\binom{n}{1}=m^{3}n>n$ and $\binom{n+m}{m}\geq \binom{n+m}{1}=n+m>n+1$. Hence $u_{n,m}>n(n+1)$.

Hence, for $1<k\leq n$, we get:

$$\begin{eqnarray*} \left\vert e_{n,k}\right\vert &=&\left\vert \sum_{m=1}^{k}\frac{(-1)^{m-1}}{% 2m^{3}\binom{n}{m}\binom{n+m}{m}}\right\vert \leq \sum_{m=1}^{k}\left\vert \frac{(-1)^{m-1}}{2m^{3}\binom{n}{m}\binom{n+m}{m}}\right\vert\leq \sum_{m=1}^{n}\frac{1}{2m^{3}\binom{n}{m}\binom{n+m}{m}}\\&<&\sum_{m=1}^{n}\frac{1}{2n(n+1)}=\frac{n}{2n(n+1)}<\frac{1}{n}. \end{eqnarray*}$$

For $k=1$, we get $\left\vert e_{n,1}\right\vert =\frac{1}{2n\left( n+1\right) }% \leq \frac{1}{2(n+1)}<\frac{1}{n}$. Thus for every integer $1\leq k\leq n$, we proved that $\left\vert e_{n,k}\right\vert <\frac{1}{n}$, which implies that $e_{n,k}$ converges uniformly in $k$ to $0$.

share|cite|improve this answer

If $k$ is fixed, all the terms are $O(1/n^2)$, and more over this is an alternating sum, so the entire sum is $O(1/n^2)$. For the uniformity I guess a more delicate argument is needed, but probably Stirling's approximation is your friend here.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.